2020
DOI: 10.3390/cancers12082232
|View full text |Cite
|
Sign up to set email alerts
|

Altered Organelle Calcium Transport in Ovarian Physiology and Cancer

Abstract: Calcium levels have a huge impact on the physiology of the female reproductive system, in particular, of the ovaries. Cytosolic calcium levels are influenced by regulatory proteins (i.e., ion channels and pumps) localized in the plasmalemma and/or in the endomembranes of membrane-bound organelles. Imbalances between plasma membrane and organelle-based mechanisms for calcium regulation in different ovarian cell subtypes are contributing to ovarian pathologies, including ovarian cancer. In this review, we focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 236 publications
0
6
0
Order By: Relevance
“…By contrast, Ca 2+ deficiency can halt cell cycle at the G 0 /G 1 and S phases (11). A number of ovarian pathologies, such as OC, typically result from the dysregulation of plasma membrane-based and organelle-based Ca 2+ signaling mechanisms (12). Ca 2+ levels have a profound effect on the physiology of the female reproductive system, especially the ovary.…”
Section: Calcium Signals and Potential Therapy Targets In Ovarian Can...mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Ca 2+ deficiency can halt cell cycle at the G 0 /G 1 and S phases (11). A number of ovarian pathologies, such as OC, typically result from the dysregulation of plasma membrane-based and organelle-based Ca 2+ signaling mechanisms (12). Ca 2+ levels have a profound effect on the physiology of the female reproductive system, especially the ovary.…”
Section: Calcium Signals and Potential Therapy Targets In Ovarian Can...mentioning
confidence: 99%
“…[Ca 2+ ]i concentrations can regulate almost every cellular process currently known, from energy production and cellular metabolism to phenotypic development. In particular, novel ideas of ovarian oncogenesis involving altered Ca 2+ signaling have been steadily proposed over the past decade (12). Variations in [Ca 2+ ]i concentrations can translate through the cell to effect distant regions, to modulate Ca 2+ signaling pathways that can regulate cell cycle progression, apoptosis, proliferation and metastasis.…”
Section: Calcium Signals and Potential Therapy Targets In Ovarian Can...mentioning
confidence: 99%
“…Calcium dysregulation can lead to a variety of diseases, including cancer [251][252][253][254]. In cancer, aberrant calcium signaling can enhance cell proliferation and angiogenesis [254,255].…”
Section: Calcium Retention Capacitymentioning
confidence: 99%
“…Calcium dysregulation can lead to a variety of diseases, including cancer [251][252][253][254]. In cancer, aberrant calcium signaling can enhance cell proliferation and angiogenesis [254,255]. Importantly, disruptions in calcium homeostasis are associated with increased apoptosis and autophagy in cancer cells [256,257], indicating that calcium dysregulation can produce effects on both ends of the spectrum.…”
Section: Calcium Retention Capacitymentioning
confidence: 99%
“…The T-type Ca 2+ channels, for example, are overexpressed in ovarian cancer where they are involved in tumor growth and its chemoresistance to platinum-based drugs [89]. Indeed, blocking T-type Ca 2+ channels with mibefradil during administration of carboplatin sensitizes platinum-resistant ovarian tumors to the anticancer drug-mediated toxicity [206]. Most studies reported in this review describe the implication of one channel in the regulation of OC development and progression.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%